2020
DOI: 10.1101/2020.11.02.365742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms underlying divergent responses of genetically distinct macrophages to IL-4

Abstract: Mechanisms by which non-coding genetic variation influences gene expression remain only partially understood but are considered to be major determinants of phenotypic diversity and disease risk. Here, we evaluated effects of >50 million SNPs and InDels provided by five inbred strains of mice on the responses of macrophages to interleukin 4 (IL-4), a cytokine that plays pleiotropic roles in immunity and tissue homeostasis. Remarkably, of >600 genes induced >2-fold by IL-4 across the five strains, only … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…While our findings largely agree with the division of serous cavity MΦ into SCM (monocyte-derived) vs LCM (tissue resident) they reveal a differentiation pathway from monocytes to LCM that differs between mouse strains. The transcriptional similarity between C57BL/6 and BALB/c SCM suggested that the core MΦ program (controlled by PU.1, C/EBPs and AP-1 binding) is relatively stable between these strains consistent with limited differences between C57BL/6 and BALB/c MΦs in response to TLR4 agonists (Link et al, 2018) and IL-4 (Hoeksema et al, 2021). However, in addition to the core MΦ program, the enhancer landscape can define a tissuespecific residency program (Gosselin et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While our findings largely agree with the division of serous cavity MΦ into SCM (monocyte-derived) vs LCM (tissue resident) they reveal a differentiation pathway from monocytes to LCM that differs between mouse strains. The transcriptional similarity between C57BL/6 and BALB/c SCM suggested that the core MΦ program (controlled by PU.1, C/EBPs and AP-1 binding) is relatively stable between these strains consistent with limited differences between C57BL/6 and BALB/c MΦs in response to TLR4 agonists (Link et al, 2018) and IL-4 (Hoeksema et al, 2021). However, in addition to the core MΦ program, the enhancer landscape can define a tissuespecific residency program (Gosselin et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…As such, the effect of host genotype on MΦ biology is relatively underexplored. Although genotype has been shown to influence the response of MΦs to Th2 cytokines (Hoeksema et al, 2021;Tang et al, 2020), these studies were not conducted in a natural type 2 immune response setting.…”
Section: Introductionmentioning
confidence: 99%
“…We next set out to determine the environmental factors that drive EGR2 expression. Many studies employing in vitro culture systems have described EGR2 expression as a feature of ‘alternatively activated’ macrophages, dependent on IL-4R signalling (3335) . Importantly, expression of EGR2 by alveolar macrophages was independent of IL-4R signalling ( Figure 5G & Supplementary Figure 5F ), as were key EGR2-dependent phenotypic traits, such as SiglecF and EpCAM expression ( Supplementary Figure 5F ).…”
Section: Resultsmentioning
confidence: 99%
“…EGR2 is consistently referred to as a feature of alternative macrophage activation induced by IL-4. Indeed, addition of IL-4 to in vitro macrophage cultures leads to upregulation of EGR2 and deletion of STAT6, a downstream adaptor molecule in the IL-4R signalling cascade, abrogates EGR2 upregulation by IL-4 treated, in vitro generated macrophages (3335) . However, mature alveolar macrophages are considered relatively refractory to IL-4 (50) and we found no effect of Il4ra deficiency on EGR2 expression in health and nor did we detect upregulation of EGR2 by interstitial macrophages which reside in the IL-4/IL-13-rich lung parenchyma during bleomycin-induced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…EGR2 transcription factor plays an important role in the regulation of Flt1 and Vegfa expression at the late phase of alternative macrophage polarization Dynamic chromatin binding of the STAT6 transcription factor was observed following the IL-4 stimulation in macrophages, showing a remarkable reduction after 24 hours of IL-4 exposure (30). In addition, it has been demonstrated that the IL-4-STAT6 signaling pathwayinduced various transcription factors, including EGR2, are crucial players in the organization of the late alternative macrophage-specific epigenetic and transcriptional program (36,56). To study whether EGR2 participates in the regulation of Vegfa and Flt1 expression in the late phase of alternative macrophage polarization, we first examined the dynamics of STAT6 and EGR2 binding at their distal regulatory regions using our previously published ChIP-seq datasets (30, 36).…”
Section: Stat6 Transcription Factor Directly Contributes To the Il-4-...mentioning
confidence: 99%